Determinants of condom use among sexually active youth in SBC intervention communities in Tanzania: A cross-sectional study - Mark Lwakatare; Gretchen Thompson; Joseph Msofe; Waziri Nyoni; Claire Gillum; Kara Tureski (PLoS ONE, 2025)
HIV and unplanned pregnancies are significant public health concerns for youth in Sub-Saharan Africa. Consistent condom use is an effective behavioral method in preventing both health outcomes; however, it remains low and is declining among this population. Evidence indicates that preventive health behaviors are influenced by a range of specific factors relevant to their contexts. This study aimed to assess factors associated with condom use among sexually active youth in communities where social and behavior change (SBC) interventions were implemented in Tanzania. A cross-sectional study was conducted among 1,959 youths aged 15–24 years, selected using a multi-stage sampling approach from three regions (Iringa, Mwanza, and Tabora) where SBC interventions were implemented. Of these, 1,265 participants (64.6%) reported sexual activity within the six months preceding the study and were included in the analysis. Multivariable logistic regression was employed to determine the significant factors associated with condom use at last sex. P-values of ≤ 0.05 were considered statistically significant. Overall, 46.9% (95% CI: 44.0–50.0) of sexually active youth reported condom use at last sex, with higher prevalences observed among those exposed to condom use messaging through social media (70.4%), and who discussed condom use with their sexual partners (63.6%) and parents (62.2%). Significant predictors of condom use included residing in Tabora (AOR = 1.609; 95% CI: 1.155–2.241), having no children (AOR = 1.844; 95% CI: 1.095–3.106), delayed sexual debut (AOR = 1.591; 95% CI: 1.027–2.464), having multiple sexual partners (AOR = 1.667; 95% CI: 1.280–2.171), having a partner tested for HIV (AOR = 1.671; 95% CI: 1.138–2.455), self-efficacy to convince partner on condom use (AOR = 1.653; 95% CI: 1.233–2.215), discussing condom use with parents (AOR = 1.902; 95% CI: 1.430–2.532), and perceived parental support in HIV prevention (AOR = 1.585; 95% CI: 1.200–2.095). Condom use among sexually active youth in Tanzania is influenced by a range of sociodemographic, behavioral, and ideational (emotional and social) factors. This indicates the continued need for tailored multi-level interventions that address the contextual needs of target audiences to improve condom use. Further research is also needed to examine the causal pathways and underlying factors influencing condom use among sexually active youth.